Nevrološka prizadetost kot dejavnik kakovosti življenja starejših pacientov z multiplo sklerozo - Koprivnik, Matej (Obzornik zdravstvene nege, 2021)
Introduction: Quality of life is an important dimension of the lives of patients with multiple sclerosis, which is influenced by several factors. The purpose of the present study is to identify the impact of neurological impairment on the physical and mental health-related quality of life of patients with multiple sclerosis aged between 50 and 59 years, and over 60.Methods: A cross-sectional study was conducted on a sample of 130 patients with multiple sclerosis, aged between 50 and 73 years. They were assessed with the Expanded Disability Status Scale, Multiple Sclerosis Quality of Life-54 (Physical and Mental Health Composite Score) and a self-designed questionnaire on the characteristics of multiple sclerosis patients. Descriptive statistics, the Kolmogorov-Smirnov test, Spearman's rank correlation coefficient and Linear regression analysis were used.Results: Neurological impairmentin patients with multiple sclerosis aged between 50 and 59 years has an impact on the physical health-related quality of life (R2 = 0.251, p < 0.001), and on the physical (R2 = 0.250, p < 0.001) and mental (R2 = 0.063, p = 0.044) health-related quality of life in patients aged between 60 and 73 years. Discussion and conclusion: After the age of 60, the impact of neurological disability extends from the physical part to the mental part of the multiple sclerosis patient's life. In order to maintain their quality of life, the physical health of patients with neurological disability between the ages of 50 and 59 should be monitored, while in patients aged between 60 and 73, their physical and mental health should be monitored.
Keywords: ageing; duševno zdravje; mental health; physical health; staranje; telesno zdravje